ROLE OF PLASTIC ZONE POROSITY AND PERMEABILITY IN SAND PRODUCTION IN WEAK SANDSTONE RESERVOIRS - Shabdirova, Ainash; Minh, Nguyen Hop; Zhao, Yong (ScienceDirect, 2022)
Sand production is often characterized as a two-stage process, in which material failure occurs near the cavity, leading to the formation of a plastic zone, from which particles are detached and transported out because of continuous hydrodynamic erosion under the effects of the produced fluid flow. The plastic zone porosity is affected by coupled processes, while the plastic zone permeability has a significant impact on the performance of sand production prediction, especially in weak sandstone reservoirs. Large-scale sand production experiments were conducted using a customized high-pressure consolidation apparatus. The results show that specific stress-fluid pressure conditions may create a plastic zone around a hole, which has lower permeability than the intact zone. The plastic zone comprises two subzones: a high-permeability shear band zone and a low-permeability compaction zone. During sand production, sand migrates from the compaction zone through the shear band zone to the perforation hole. Thus, sand production is associated with the increased permeability and porosity in the compaction zone. Existing sand prediction models were modified according to the new findings, resulting in a modified model with improved performance. The modified model was validated using the sanding data from a weak sandstone reservoir in Kazakhstan.
Keywords: Type of access: Open Access; Sand production; Plastic zone; Weak sandstone; Porosity; Permeability